2019
DOI: 10.1002/sctm.18-0220
|View full text |Cite
|
Sign up to set email alerts
|

Stable Intracerebral Transplantation of Neural Stem Cells for the Treatment of Paralysis Due to Ischemic Stroke

Abstract: NSI‐566 is a stable, primary adherent neural stem cell line derived from a single human fetal spinal cord and expanded epigenetically with no genetic modification. This cell line is being tested in clinical trials in the U.S. for treatment of amyotrophic lateral sclerosis and spinal cord injury. In a single‐site, phase I study, we evaluated the feasibility and safety of NSI‐566 transplantation for the treatment of hemiparesis due to chronic motor stroke and determined the maximum tolerated dose for future tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…Our results are in line with MRI data from our previous clinical study, which showed atrophy within peri-infarct areas and secondary dilations of the adjacent ventricle were less prominent in MSC-treated patients than in control patients [ 48 ]. A recent small study showed cavity-filling by new neural tissue formation in patients who received intracerebral injection of a neural stem cell line [ 49 ]. Jiang and colleagues used DTI techniques to measure white matter recovery after stem cell therapy in a rat stroke model [ 22 ], and Chen and colleagues undertook a stem cell therapy clinical study and showed that DTI fiber number asymmetry scores were correlated with functional recovery, and were reduced in patients who received stem cells [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in line with MRI data from our previous clinical study, which showed atrophy within peri-infarct areas and secondary dilations of the adjacent ventricle were less prominent in MSC-treated patients than in control patients [ 48 ]. A recent small study showed cavity-filling by new neural tissue formation in patients who received intracerebral injection of a neural stem cell line [ 49 ]. Jiang and colleagues used DTI techniques to measure white matter recovery after stem cell therapy in a rat stroke model [ 22 ], and Chen and colleagues undertook a stem cell therapy clinical study and showed that DTI fiber number asymmetry scores were correlated with functional recovery, and were reduced in patients who received stem cells [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…(2) Cell therapy, such as intravenous or arterial injection of monocytes cells and mesenchymal stromal cells [38][39][40][41][42][43][44][45][46][47], injection of olfactory ensheathing cells (OECs) into olfactory sub-mucosa [48], and neural stem cells injection around the diseased region [49][50][51], is suitable for patients with stroke with mild, moderate, and severe neurological damage. Recent studies on high-level evidence-based medicine did not show the neurorestorative capability of mesenchymal stem cells for stroke during the recovering phase.…”
Section: Recovery Phasementioning
confidence: 99%
“…Levy et al [14] reported that intravenous allogeneic mesenchymal stem cells [i.e., mesenchymal stromal cells (MSCs)] improved the neurological behaviors of patients with chronic stroke and substantial functional deficits. Zhang et al [15] showed that the intracerebral injection of neural stem cells improved the neurological functions of patients with paralysis after an ischemic stroke. Guo et al [16] reported that transplanting olfactory ensheathing cells in a patient with cerebral infarction sequela could improve his quality of life.…”
Section: Achievements and Progress In Clinical Neurorestorative Therapies 41 Cell Therapymentioning
confidence: 99%